2018
DOI: 10.1183/16000617.0113-2017
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio and clinical outcomes in COPD: recent evidence and future perspectives

Abstract: Chronic obstructive pulmonary disease (COPD) is a disabling condition that is characterised by poorly reversible airflow limitation and inflammation. Acute exacerbations of COPD are a common cause of hospitalisation and death among COPD patients. Several biochemical markers have been studied as outcome predictors in COPD; however, their measurement often requires significant time and resources. Relatively simple biomarkers of inflammation calculated from routine complete blood count tests, such as the neutroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
144
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(151 citation statements)
references
References 56 publications
4
144
3
Order By: Relevance
“…This simple test can be used to evaluate the severity of the disease and to identify critically affected patients as a result of systemic inflammation. Recent studies have shown that NLR values are highly associated with prognosis of diseases that are related to inflammation such as preeclampsia, endometriosis, chronic obstructive pulmonary disease, appendicitis and various types of cancers …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This simple test can be used to evaluate the severity of the disease and to identify critically affected patients as a result of systemic inflammation. Recent studies have shown that NLR values are highly associated with prognosis of diseases that are related to inflammation such as preeclampsia, endometriosis, chronic obstructive pulmonary disease, appendicitis and various types of cancers …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that NLR values are highly associated with prognosis of diseases that are related to inflammation such as preeclampsia, endometriosis, chronic obstructive pulmonary disease, appendicitis and various types of cancers. [9][10][11][12][13] In previous reports, white blood cell (WBC) count, C-reactive protein (CRP) levels, sedimentation values, body temperature and TOA diameter were investigated for evaluating the risk factors that cause failure of antibiotic therapy in TOA patients, however, the NLR has not been studied, yet. 14,15 The aim of this study is to compare the NLR in TOA patients who were cured after medical treatment or who underwent surgery or interventional radiologic abscess drainage due to medical treatment failure.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil-to-lymphocyte ratio (NLR) is another parameter used to evaluate inflammatory status.7 Despite numerous studies conducted in adults, few studies have evaluated NLR in childhood. 21,22 Moreover, most pediatric studies have focused on NLR in asthma. 23,24 Like studies measuring MPV levels, different results have been reported on NLR in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…White blood cell count, neutrophil-to-lymphocyte ratio, and eosinophil-to-basophil ratio were used as inflammatory biomarkers, given their established role in the pathogenesis of COPD. [46][47][48] Individual-level sociodemographic covariates comprised age, sex, highest qualification, and employment status. Highest qualification was a five-factor variable (coded as none; O levels, General Certificate of Secondary Education, or Certificate of Secondary Education; A levels or AS levels; National Vocational Qualification, Higher National Diploma, Higher National Certificate, or other profess ional qualification; college or university degree), while employment status was a three-factor variable (coded as employed; retired; and unemployed, home maker, others).…”
Section: Methodsmentioning
confidence: 99%